Use of osteogenic bone matrix in patients with traumatic long bone defects: An open label, single center study - Murdoch, Marshall; Wittstock, Craig; Psaras, George; Widgerow, Alan; Lukhele, Mkhululi; Ramokgopa, Mmampapatla Thomas; Snyman, Jacques; Hutchings, Jane; Marcos, Elizabeth; Grisillo Biscardi, Anna; Cromarty, Duncan; Zheng, Xu; et al. (Journal of orthopaedics, 2025)
Osteogenic Bone Matrix (Altis™ OBM) is a tissue-engineered, porcine-derived demineralized bone matrix prepared using a humanization processing technology that confers biocompatibility and improved osteoinductivity. The objective of this study was to determine the safety and efficacy of OBM in patients with traumatic long bone defects in an open-label, non-randomized single-center study. Diagnosis and main criteria for inclusion were open long bone fractures graded as Gustilo-Anderson Grade II, IIIA or IIIB. 24 participants were enrolled from one center, of which 17 were assigned to the investigational group (OBM) and 7 to the standard of care (SOC) group. Participants were followed at intervals of one, two, six, and 13 weeks to undergo physical examinations and record adverse events, vital signs, electrocardiograms, hematology, blood biochemistry and circulating humoral antibodies against human and porcine Type I and II collagens. Efficacy of treatment over six months post-surgery was assessed by a panel of blinded radiologists to determine the proportion of subjects with radiographic bridging of fractures in both the OBM efficacy group and the SOC group. Limb function, weight-bearing, pain and mobility at the fracture site were assessed by the investigator. Patient satisfaction with the treatment and quality of life were assessed using the SF 36 quality of life questionnaire. 14 OBM patients and five SOC patients completed the first three months of the safety investigation. 10 OBM patients and four SOC patients completed the full six months of the efficacy investigation. Biochemical and hematological parameters were within normal ranges. The efficacy evaluation at six months indicated that 70 % of participants in the OBM group had bridging of the bone defect and 80 % were weight-bearing versus 50 % in the SOC group. The quality of life study demonstrated an increased level of satisfaction as compared with the baseline. Histological analysis of a single biopsy specimen at three months revealed bone regeneration activity within the implanted OBM. The study showed that treatment with OBM was well tolerated in participants and there was no evidence of clinically relevant toxicity or immunological, biochemical, hematological or adverse reaction due to the use of OBM. There was better bridging in the OBM group versus SOC. Pharmacoeconomic analysis showed OBM to be cost-effective versus standard of care. Medicines Control Council of South Africa (MCC number N2/19/8/2).